Productivity effect of efficiency wages at small and medium-sized manufacturing enterprises: The case of Vietnam - Tung Nhu Nguyen (Global Business & Finance Review (GBFR), 2023)
Purpose: This paper aims to investigate whether efficiency wages for production workers have a positive effect on labor productivity in Vietnam's manufacturing SMEs. Design/methodology/approach: The research analyzes the panel data of manufacturing SMEs collected by UNU-Wider in Vietnam in 2011, 2013, and 2015. Findings: The panel-data analysis results for 6,953 observations show that efficiency wages increase labor productivity. Research limitations/implications: The scope of this study is limited to Vietnam's manufacturing SMEs. Future studies should include replicating the research model in the service sectors and other countries. Originality/value: Previous studies on Vietnamese manufacturing SMEs did not disclose the impact of efficiency wages on firm-level labor productivity using the SME panel datasetVietnam's. The novelty of this study is the introduction of the efficiency wages as an explanatory variable forto labor productivity. The study results shed light on organizational behavior in rational salary decisions. Many of SMEs have decided to pay lower than the average sector wage. NeverthelsessStill, the regression analysis indicates that salary growth improves per-worker productivity. This discovery allows researchers to investigate why SMEs have decided not to raise worker wages significantly while wage increases helps boost labor productivity. As a practical contribution, the study result recommends that for higher labor productivity at lower labor costs, manufacturing SMEs can raise their workers' salaries based on the average sector wage instead of benchmarking them with the average nation-level wages.
Keywords: 650; Labor productivity; Efficiency wage; Small and medium-sized enterprises; Manufacturing; Vietnam